2017
DOI: 10.3892/or.2017.5444
|View full text |Cite
|
Sign up to set email alerts
|

A novel cycloartane triterpenoid from Cimicifuga induces apoptotic and autophagic cell death in human colon cancer HT-29 cells

Abstract: The extract from Cimicifuga, a genus of flowering plants, has been demonstrated to have mainly therapeutic effects on menstrual and menopausal symptoms and also exhibits immunomodulatory, anti-inflammatory and antimicrobial activity. Moreover, the anticancer effects of Cimicifuga have been reported, but the underlying mechanism causing cancer cell death has been poorly described. The present study was designed to investigate the antitumor effects and underlying molecular mechanisms of cimigenol (KY17), a novel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…However, the effect of pristimerin on autophagy in human breast cancer has not been fully understood. Certain studies have reported that triterpenoids can cause cell death by autophagy, including cimigenol (KY17) ( 22 ), 2α, 3α, 24-thrihydroxyurs-12-en-28-oicacid ( 23 ), ursolic acid ( 24 ) and cucurbitane ( 25 ). In the present study, the autophagic effect of pristimerin on MDA-MB-231 human breast cancer cells was examined.…”
Section: Discussionmentioning
confidence: 99%
“…However, the effect of pristimerin on autophagy in human breast cancer has not been fully understood. Certain studies have reported that triterpenoids can cause cell death by autophagy, including cimigenol (KY17) ( 22 ), 2α, 3α, 24-thrihydroxyurs-12-en-28-oicacid ( 23 ), ursolic acid ( 24 ) and cucurbitane ( 25 ). In the present study, the autophagic effect of pristimerin on MDA-MB-231 human breast cancer cells was examined.…”
Section: Discussionmentioning
confidence: 99%
“…5(c) and 5(d) highlighting our depth-sectioned and high-resolution reconstructions. Dark granules ultrastructural features reported for HT29 cells include microvilli, large vacuolated mitochondria with dark granules, smooth and rough endoplasmic reticulum with free ribosomes, lipid droplets, and few primary and many secondary lysosomes [51,52]. Line profiles across multiple reconstructed slices in Figs.…”
Section: Tomographic Characterization Of Ht29mentioning
confidence: 92%